(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2010)
IF we called twentieth century, the century of productivity and information revolution, the suitable address for twenty-first century is (( The quality century )) . The research aims to initiate Arabic prize for quality to apply concepts and strategies of total quality management at Higher education sector, which is a vital sector and it may be the most importance sector because it provide efficient human manpower working at all other sectors. The suggested prize take in consideration the specialty of this sector, and when we apply perspectives of this prize this will promote Arabic universities performance as well as the quality of graduates. The importance of this research due to the necessity of this prize especially we never have such prize for Higher education Arabic sector.